The influence of thyroarytenoid and cricothyroid muscle activation on vocal fold stiffness and eigenfrequencies - Yin, Jun (Acoustical Society of America, 2013)
The influence of the thyroarytenoid (TA) and cricothyroid (CT) muscle activation on vocal fold stiffness and eigenfrequencies was investigated in a muscularly controlled continuum model of the vocal folds. Unlike the general understanding that vocal fold fundamental frequency was determined by vocal fold tension, this study showed that vocal fold eigenfrequencies were primarily determined by vocal fold stiffness. This study further showed that, with reference to the resting state of zero strain, vocal fold stiffness in both body and cover layers increased with either vocal fold elongation or shortening. As a result, whether vocal fold eigenfrequencies increased or decreased with CT/TA activation depended on how the CT/TA interaction influenced vocal fold deformation. For conditions of strong CT activation and thus an elongated vocal fold, increasing TA contraction reduced the degree of vocal fold elongation and thus reduced vocal fold eigenfrequencies. For conditions of no CT activation and thus a resting or slightly shortened vocal fold, increasing TA contraction increased the degree of vocal fold shortening and thus increased vocal fold eigenfrequencies. In the transition region of a slightly elongated vocal fold, increasing TA contraction first decreased and then increased vocal fold eigenfrequencies.